Tracing iron ore tailings in the marine environment: An investigation of the Fundão dam failure. (October 2020) - D′Azeredo Orlando, Marcos Tadeu; Galvão, Elson Silva; Sant′Ana Cavichini, Arthur; Gabrig Turbay Rangel, Caio Vinícius; Pinheiro Orlando, Cintia Garrido; Grilo, Caroline Fiório; Soares, Jacyra; Santos Oliveira, Kyssyanne Samihra; Sá, Fabian; Junior, Adeildo Costa; Bastos, Alex Cardoso; da Silva Quaresma, Valeria
Abstract: This work aims to characterize, in mineral and chemical terms, the ore tailings related to the Mariana disaster (MG, Brazil), occurred on 5 November 2015, and assess its correlation with sediments found in the continental shelf adjacent to the Doce River mouth (ES, Brazil). This study uses samples of tailings and seabed sediments collected at the mouth of the Doce River from 2012 to 2019. Elemental compositions of all samples were determined by X-ray fluorescence measurements; however, Synchrotron Resonant X-Ray Diffraction proved to be a remarkable technique to characterize the crystallographic phases of iron present in sediments. Studies and analyzes of the sediment samples showed that the tailings have a notable feature of the iron-crystallographic phases, mainly observed in the period after the Fundão dam failure, as compared with sediments collected in the period before. This set of iron-containing mineral phases, here called the Iron Mineralogical Set (IMS), consists of the main phases of hematite and magnetite and the minority phases of goethite and greenalite and it is used as a marker of tailings. Mass ac magnetic susceptibility measures supported the concept of the IMS as a marker. It is suggested a relationship between the content of the IMS in the sediment samples as a function of the measures of mass magnetic susceptibility. The IMS had shown the influence of tailings on the sea bed sediment indicating that there is no possibility, at the current stage, of predicting how many years this material will still be at the seabed. Highlights: Tailings are mainly featured by iron-crystallographic phases. Diffraction patterns at different energies show higher contrast of the iron phases. It is hard to predict how long the tailings will persist in the marine environment.